Penerapan Lubang Resapan Biopori Sebagai Upaya Peningkatan Kualitas Lingkungan di Desa Darmaji - Arben Virgota; Baiq Farista; Rina Kurnianingsih; Baiq Mira Permata Sari; Ismira Anestia Iskandar (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
Darmaji Village is one of the villages on the island of Lombok which has potential in the field of food and the environment. The main problem in the environmental sector is the presence of standing water in residential areas during the rainy season and the low level of waste utilization. Efforts to overcome this are the application of bio pure infiltration holes that can act as water absorption media, increase groundwater reserves, and compost media in Darmaji village. The method of implementation is by making several pilot locations and socialization through brochures and leaflets. The results of this activity made many residents interested in applying biopori in their homes. So it is hoped that in the future it can overcome environmental problems and support tourism activities on the island of Lombok in Darmaji Village.